Mathematics Content Knowledge Guru Sekolah Menengah: Konteks Peluang dan Kombinasi - Soffil Widadah; Aunillah (JEDMA Jurnal Edukasi Matematika, 2023)
Secondary school teachers need to have strong Mathematics Content Knowledge of chance and combination to teach effectively and help students understand the concepts. This study aims to describe the correlation between Mathematics Content Knowledge of senior and junior secondary school teachers. The research subjects in this study were 17 secondary school teachers consisting of senior and junior teachers. The results were analyzed using Pearson Correlation to describe the relationship between MCK and teacher tenure. Furthermore, two subjects (one senior teacher and one junior teacher) were taken to be interviewed and described the ability to solve chance and combination problems. The results showed that there was no correlation between MCK and teacher seniority. In the context of chance, r , while in the context of combination r . Based on the test and interview results, it was found that senior teachers performed the algorithm more sequentially and completely than junior teachers. This can be caused by the readiness of senior teachers in solving the problems given. The researcher hopes that there will be further research with more subjects and more varied materials.